Blast Waves - Needham, Charles E. (Shock Wave and High Pressure Phenomena,, 2018)
This book examines blast waves-their methods of generation, their propagation in several dimensions through the real atmosphere and layered gases, and their interactions with simple structures-thereby providing a broad overview of the field. The intended audience has a basic knowledge of algebra and a good grasp of the concepts of conservation of mass and energy. The text includes an introduction to blast wave terminology and conservation laws, and there is a discussion of units and the importance of consistency. This new edition of Blast Waves has been thoroughly updated and includes two new chapters that cover numerical hydrodynamics and blast injury. Authored by an expert with over forty years of experience in the field of blast and shock, this book offers many lessons as well as a historical perspective on developments in the field.